2015
DOI: 10.1159/000374108
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Style Selectively Shapes Amygdalar Development and Social Behavior in Rats Genetically Prone to High Anxiety

Abstract: The early-life environment critically influences neurodevelopment and later psychological health. To elucidate neural and environmental elements that shape emotional behavior, we developed a rat model of individual differences in temperament and environmental reactivity. We selectively bred rats for high versus low behavioral response to novelty and found that high-reactive (bred high-responder, bHR) rats displayed greater risk-taking, impulsivity and aggression relative to low-reactive (bred low-responder, bL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 52 publications
3
53
2
Order By: Relevance
“…highly exploratory and impulsive) vs. low responders (LH; e.g. heightened anxiety- and depressive-like behavior), cross-fostering at birth between HR and LR results in reduced anxiety-like behavior and altered gene expression in the amygdala of LR offspring reared by HR dams [139]. In mice selectively bred for alcohol preference [high alcohol preference (HAP) vs. low alcohol preference (LAP)], cross-fostering at birth indicates that HAP pups reared by LAP dams have reduced levels of alcohol preference.…”
Section: Timing and Sensitive Periodsmentioning
confidence: 99%
“…highly exploratory and impulsive) vs. low responders (LH; e.g. heightened anxiety- and depressive-like behavior), cross-fostering at birth between HR and LR results in reduced anxiety-like behavior and altered gene expression in the amygdala of LR offspring reared by HR dams [139]. In mice selectively bred for alcohol preference [high alcohol preference (HAP) vs. low alcohol preference (LAP)], cross-fostering at birth indicates that HAP pups reared by LAP dams have reduced levels of alcohol preference.…”
Section: Timing and Sensitive Periodsmentioning
confidence: 99%
“…Sprague Dawley rats that were selectively bred to display low behavioral response to novelty (Low Responders, LR) also exhibit high anxiety- and depression-like behavior compared to High Novelty Responder rats (HRs). These behaviors include diminished sociability and sexual motivation, increased behavioral inhibition and helplessness, as well as greater vulnerability to chronic stress (Stead et al, 2006a, Stedenfeld et al, 2011, Cummings et al, 2013, Clinton et al, 2014, Cohen et al, 2015). Furthermore, these behavioral traits emerge in early life, and a previous microarray study from our group revealed widespread gene expression differences in the early postnatal HR versus LR brain (Clinton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work suggested that HR/LR differences in anxiety/depression-like behavior stem from disparate developmental trajectories in the early postnatal hippocampus and possibly amygdala (Clinton et al, 2011, Cohen et al, 2015). These early life HR/LR gene expression differences involved several functional classes of genes, including those relevant to synaptogenesis, synaptic plasticity, and cellular metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, hypoglycemia is a potent stressor and leads to robust corticosterone response in three-week-old rats [51]. Early life stress negatively influences regional gene expression and behavioral performance, and is known to suppress BDNF expression in the PFC [52–55]. Future studies are necessary to address all these possibilities.…”
Section: Discussionmentioning
confidence: 99%